(untitled) (Research, Society and Development, 2021)
In view of the reports on the use of germline genetic information in preventive and treating this type of carcinoma, as well as their potential as patterns of genetic markers analogous to expression profiles obtained from tumor tissue, allowing a more powerful prediction who will respond best to a specific treatment or regimen. Thus, this study aims to assess the importance of pharmacogenetics in the treatment of breast cancer. This is a literature review, where the following databases were used: MEDLINE, LILACS and Scielo, in which publications in Portuguese and English were selected between 2016 and 2021. Through the results obtained, it was observed that the introduction of pharmacogenetics in oncology has enabled the development of a new generation of pharmacological agents capable of being selective against neoplastic cells, enabling a significant improvement in the risk/benefit ratio of numerous types of cancer, particularly breast cancer. Thus, the role of the pharmacist becomes essential in Pharmacogenetics when associated with clinical practice, as he is a health professional who has a full understanding of the phenomena that occur in this category, contributing to the assistance of other components of the functional health group , performing a plausible interpretation of the analysis results and their subsequent applicability.